WELFARE, HEALTH, AND THE MORAL CONSIDERABILITY OF NONSENTIENT BIOLOGICAL ENTITIES - DUSSAULT, ANTOINE (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2018)
This paper discusses a challenge to the claims made by biocentrists and some ecocentrists that some nonsentient biological entities (e.g., organisms, species, ecosystems) qualify as candidates for moral considerability. This challenge derives from Wayne Sumner’s (1996) critique of “objective theories of welfare” and, in particular, from his critique of biocentrists’ and ecocentrists’ biofunction-based accounts of the “good of their own” of nonsentient biological entities. Sumner’s critique lends support to animal ethicists’ typical skepticism regarding those accounts, by contending that they are more plausibly interpreted as accounts of the perfectionist value than of the welfare of nonsentient biological entities. In response to this critique and its implication that those function-based accounts would fail to qualify nonsentient biological entities as candidates for moral considerability, it is argued that those accounts should be interpreted as ones of the health of biological entities rather than ones of their perfectionist value. It is suggested that their being bearers of health may be sufficient for nonsentient biological entities to qualify as candidates for moral considerability, such that biocentrists and ecocentrists could grant Sumner and animal ethicists’ contention that the function-based accounts of the good of their own of nonsentient biological entities are not accounts of their welfare, while not giving up on the project of defending those entities’ moral considerability.